Combating hospital-acquired C. diff. Issue 3 (March 2018) - Johnson, Shelley
Abstract : A successful collaboration between clinical nurse leaders and clinical nurse specialists Abstract : Find out how clinical nurse leaders and clinical nurse specialists at one community hospital successfully collaborated to address high C. difficile infection rates.